Эволюция концепта скуки в творчестве Елены Шварц - Vorontsova, Kristina (Studia Rossica Posnaniensia, 2023)
This paper focuses on the concept of boredom in the creative work of one of the significant figures of Soviet underground culture – Elena Shvarts. All the creative heritage – both poetic and prosaic – is treated like a semiotic unity, so that it is possible to see the evolution in understanding such a notion during more than five decades of the poet’s life. While analyzing the five-volume collection by Shvarts, statistical calculation has revealed only 28 cases of using the concept. Even though for Shvarts’s lyrical subjects, who are usually passionate and ecstatically active, boredom is not specific at all, the author sometimes puts this concept in the meaningful center of her creative universe. It could be done both explicably and implacably through the description of “boring” landscapes and events. After close reading of the texts from the five-volume collection, it is claimed that boredom in Shvarts’s oeuvre is strictly associated to the physical (and\or physiological) world, with its routines, wishes and activities. To the contrast, the transcendental world and everything connected to the sacrum, according to Elena Shvarts, cannot be boring.